The Role of Platelet Concentrates and Growth Factors in Facial Rejuvenation: A Systematic Review with Case Series - Giuseppina Malcangi; Angelo Michele Inchingolo; Alessio Danilo Inchingolo; Laura Ferrante; Giulia Latini; Irma Trilli; Paola Nardelli; Marialuisa Longo; Andrea Palermo; Francesco Inchingolo; Gianna Dipalma (Medicina)
Background and objectives: Due to the regeneration potential of growth factors (GFs) and platelet concentrates (PCs), facial rejuvenation has been a major area of attention in esthetic medicine. The effectiveness and safety of PCs and GFs in promoting face rejuvenation are examined in this systematic review, which is complemented by a case series. GFs are essential for collagen production and dermal matrix remodeling, while PCs, like Platelet-Rich Plasma (PRP), are abundant in bioactive chemicals that promote tissue healing and cellular regeneration. Materials and Methods: A comprehensive literature search was performed on PubMed, Web of Science, and Scopus, focusing on human clinical trials published between February 2019 and February 2024 related to PRP and facial esthetics. Results: Thirteen studies met the inclusion criteria and were analyzed. Conclusions: The review summarizes the most recent data on patient outcomes, treatment regimens, and possible hazards. The case series that goes with it shows real-world examples of how to improve skin elasticity, texture, and general facial appearance with little negative side effects. These results highlight the potential use of PCs and GFs as minimally invasive procedures.